Respon Populasi Asal Cendana (Santalum album L) terhadap Serangan Embun Jelaga - Fiani, Ari; Yuliah, Yuliah -; Hadiyan, Yayan (Universitas Sebelas Maret, 2017)
Black Mildew attacks have been suspected to disturb the growth of Sandalwood (Santalum album) ex situ conservation in GunungKidul, as this disease can inhibit the process of photo synthesis. The origins of Sandalwood's population collected in 2005 are expected to have variety of resistance to the attack. Research has been undertaken to know the impact of black mildew on two observation period that is in rainy season and dry season. The data were collected with 100% sampling intensity in 4 population of sandalwood from 4 replications. The results showed that the intensity of black mildew in the rainy season ranged from 59.34% (Timor Tengah Utara) to 87.86% (Sumba). In June when the rainfall started to decrease, the intensity of black mildew attacks ranged between 51.34% (Belu) to 72.83% (Sumba). The Sumba population has the lowest resistance compared to Belu and Rote populations. The variation in the severity of black mildew is not related to the origin of the population, but due to leaf age.